Nanowires building blocks for nanoscience and nanotechnology - Zhang, Anqi; Zheng, Gengfeng; Lieber, Charles M. 1959- (NanoScience and technology, 2016)
Emergence of Nanowires -- Synthesis and Characterization -- Hierarchical Organization -- Nanoelectronics, Circuits and Nanoprocessors -- Nanophotonics (Passive and Active Devices) -- Quantum Devices -- Nano-Enabled Energy -- Nano-Bio Interfaces -- Conclusions and Outlook